Sistem Pencatatan Penyewaan Truk Peti Kemas Berbasis Aplikasi Desktop di PT. Contena Sekawan Anekatrans - Irvan Fadil Haris; Harfebi Fryonanda (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
At PT. Contena Sekawan Anekatrans, data recording is still written on paper which makes the data recording could not be completed quickly. Researcher create a system of trucking recording based on desktop application at the company to simplify and quickly in trucking recording at the company. The method in making this application uses the System Development Life Cycle method with the Prototype technique which consists of six stages, namely problem identification, problem analysis, system prototype design, system development, system testing, and system implementation. This system of trucking recording was created using the Java Netbeans IDE and MySQL applications. The expected benefit is, this system of trucking recording based on desktop apllication can facilitate the work of the employees of PT. Contena Sekawan Anekatrans to make trucking recording more efficient. This trucking recording was tested using the Black Box Testing method.